The Contribution of Productive Zakat in Overcoming Poverty Using The Had Kifayah Method at The Kampung Zakat Sumber Jambe Jember Institution - Miftahus Surur; Nur Fatiha; Asytia Haninah; Puji Purnawan; Gunawan, Gunawan (CV. Ulil Albab Corp, 2025)
Islamic economic principles help individuals set life goals and follow values based on Islamic teachings. One important tool in Islamic economics is zakat, which helps address social and economic problems. zakat can be a powerful way to fight poverty and inequality. However, every year, there is ongoing debate and evaluation about its role and impact. The research uses a descriptive qualitative approach, utilizing field research to gather data. The data collection methods include interviews, observations, and documentation. The research is conducted in Kampung Zakat Sumber Jambe, Jember, providing an in-depth analysis of how zakat is implemented and its effects on the community. The productive zakat contributions in Kampung Zakat aim to empower mustahik through various initiatives, such as business training in skills like making rattan woven bags and paving and brick-making, providing capital to start businesses, and offering 15 goats to each mustahik, with proceeds from sales split between the mustahik and the manager. However, the program faces several challenges, including a lack of coordination, insufficient facilities, and limited funds. To address these issues and improve the program’s implementation, solutions such as enhancing coordination, increasing facilities, and securing sufficient funds are crucial for ensuring the program’s success and sustainability.